Exposing Literacy in SD and SMP Swasta HKBP Sidorame Medan - Manurung, Lastri Wahyuni; Sitorus, Nurhayati; Pangaribuan, Marnala; Pakpahan, Carolina; Saragi, Christina Natalina; Sipayung, Kammer Tuahman; Napitupulu, Fenty Debora; Maděra, Martin (UKInstitute, 2022)
The program of Pengabdian Kepada Masysarakat (Public Community Service) is aimed the literacy improvement training for elementary and junior high school children aims to provide students as well as teachers with information assistance about the importance of literacy for the development of knowledge in Indonesian society. This activity was carried out by lecturers and students from the English Department, Faculty of Teacher Training and Education, HKBP Nommensen University with students from Czech University. The program of PKM Activity was started on July 25th, 2022, and ended on July 26th, 2022. It is very clear that the cause of the low literacy ability (in terms of reading) is the oral tradition that is still rooted in society. In addition, related to elementary schools, the school system still does not provide opportunities for literacy traditions to students. This also happened to students at SD and SMP HKBP Sidorame Medan. This problem is trying to be minimized by conducting community service programs related to literacy for elementary and junior high school students. The Project represents one of the important areas of development of reading literacy in school. The most positive feature is the fact that there are large numbers of identified target groups, not only students but also teachers. Teachers themselves should expose students to literacy. Literacy should become a culture.